2001
DOI: 10.1002/hipo.1059.abs
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of isolation‐induced hypertension by intrahippocampal administration of a nonpeptide kappa‐opioid receptor agonist

Abstract: Previous research in this laboratory showed that hypertension in the spontaneous hypertensive rat (SHR) appears to correlate to insufficient production of hippocampal dynorphins, and that blood pressure could be reduced by intrahippocampal administration of dynorphins and nonpeptide kappa agonists. The purpose of the present study was to investigate whether kappa agonists could prevent the development of hypertension in a different hypertensive model, i.e., the isolated male rat model of hypertension (IHR). Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…κ-opioid receptor (Privette and Terrian 1995;Wright and Ingenito 2001;Wall and Messier 2000), and ORL 1 receptor (Jenck et al 1997;Jenck et al 2000;Wichmann et al 2000, but see Fernandez et al 2004) have been shown to increase the percentage of entries and time spent in the open arms of a plus maze, indicating an anxiolytic-like action.…”
mentioning
confidence: 97%
“…κ-opioid receptor (Privette and Terrian 1995;Wright and Ingenito 2001;Wall and Messier 2000), and ORL 1 receptor (Jenck et al 1997;Jenck et al 2000;Wichmann et al 2000, but see Fernandez et al 2004) have been shown to increase the percentage of entries and time spent in the open arms of a plus maze, indicating an anxiolytic-like action.…”
mentioning
confidence: 97%